Kajian Potensi Lanskap Desa Kamal Kecamatan Arjasa Kabupaten Jember untuk Pengembangan Wisata Sejarah Berbasis Masyarakat - Violetta, Fransiska Rona; Makalew, Afra Donatha Nimia; Budiarti, Tati (http://arl-faperta.ipb.ac.id/, 2024)
Jember is one of the regencies located in East Java. Jember seeks to explore new tourism potentials that have not been widely developed, including in the field of historical and cultural tourism. This potential can be found in Kamal Village, Arjasa Sub-district. The purpose of this study was to assess the landscape potential of Kamal Village as an initial analysis of the development of a community-based historical tourism area. The analysis used includes land suitability analysis, historical analysis, thermal humidity index analysis, and community acceptability analysis. Based on the results of the analysis, the general condition of Kamal Village has the potential to be developed as a tourist area. Kamal Village has cultural heritage objects in the form of kenong stones, dolmen stones, menhir stones, lumpang stones, direction stones, and slate stones. All of these cultural heritage sites are quite feasible in terms of their historical value. There are two arts and cultures in Kamal Village that can be used as additional tourist attractions in the form of the Kadisah Ritual and Ta'Butaan. Regarding community acceptability, 100% of villagers agreed with the development of the area as a tourist destination. A total of 86.67% are very willing to play an active role in tourism. Therefore, Kamal Village has high potential to be developed as a community based historical tourism area.